Reconciling Occupational Mobility in the Current Population Survey - Christian vom Lehn; Cache Ellsworth; Zachary Kroff (Institute of Labor Economics (IZA), 2020)
Measuring occupational mobility from the Current Population Survey using recall (retrospective) or linked panel responses (longitudinal) generates substantially different outcomes, both in levels and trends. Using a generalized method of moments technique, we estimate the actual level of occupational mobility and the measurement error in both of these measures for 1981-2018. Measurement error in longitudinal measures is large and has been worsening over time. However, actual occupational mobility is approximately 70% higher than retrospectively measures. Our estimated corrections imply workers in tradable occupations are less likely to switch occupations than previously believed, implying potentially lower welfare gains from trade.
Keywords: J62; C83; F16; 330; occupational switching; worker mobility; current population survey; measurement error; trade adjustment